The Complex Clinical Issues Involved in an Athlete’s Decision to Retire from Collision Sport Due to Multiple Concussions: A Case Study of a Professional Athlete - Gardner, Andrew (Frontiers in Neurology, 2013)
The issue of retirement from athletic participation due to repetitive concussive injuries remains controversial. The complexity of providing recommendations to elite athletes is highlighted by the prospect that offering inappropriate advice may foreseeably lead to engagement in a medico-legal challenge. Currently no evidenced-based, scientifically validated guidelines for forming the basis of such a decision exist. The current paper discusses the complexities of this challenge in addition to presenting a case study of a professional athlete. A number of central issues to consider when discussing athlete retirement revolve around the player’s medical and concussion histories, the current clinical profile, the athlete’s long-term life goals, and understanding of the potential long-term risks. Ensuring that thorough investigations of all possible differential diagnosis, that may explain the presenting symptoms, are conducted is also essential. Discussion pertaining to recommendations for guiding the clinical approach to the retirement issue for athletes with a history of multiple concussions is presented.